PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI ONLINE SHOP CALLATHRIF NGANJUK - Erlisa, Dina Olivia Nur; Paramitha, Dyah Ayu (Universitas Nusantara PGRI Kediri, 2023)
The main objective of this research is to assess the impact of different factors like service quality, pricing, and promotions on the purchasing decisions made by customers at the online shop, Callathrift Nganjuk. The research adopts a quantitative approach with a focus on establishing causal relationships. A total of 40 consumers were selected for the study using the accidental sampling method. Data analysis involved a range of statistical techniques, including validity tests, reliability tests, descriptive analysis, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing through SPSS version 25. The findings indicate that service quality has a significant partial influence on purchasing decisions. However, price does not exert a significant impact on purchasing decisions when considered individually. Similarly, promotions also do not significantly influence purchasing decisions when examined separately. Nevertheless, when considered together, service quality, pricing, and promotions collectively demonstrate a significant influence on purchasing decisions. Keywords: Service Quality, Price, Promotion, Purchase DecisionThe main objective of this research is to assess the impact of different factors like service quality, pricing, and promotions on the purchasing decisions made by customers at the online shop, Callathrift Nganjuk. The research adopts a quantitative approach with a focus on establishing causal relationships. A total of 40 consumers were selected for the study using the accidental sampling method. Data analysis involved a range of statistical techniques, including validity tests, reliability tests, descriptive analysis, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing through SPSS version 25. The findings indicate that service quality has a significant partial influence on purchasing decisions. However, price does not exert a significant impact on purchasing decisions when considered individually. Similarly, promotions also do not significantly influence purchasing decisions when examined separately. Nevertheless, when considered together, service quality, pricing, and promotions collectively demonstrate a significant influence on purchasing decisions.Keywords: Service Quality, Price, Promotion, Purchase Decision